(untitled) (Global Journal of Science Frontier Research, 2021)
This paper is an investigation of the test of unit roots with trend break functions without a priori information in some selected macroeconomic variables in Nigeria. These variables are interest rate, inflation rate, exchange rate, real gross domestic product, and unemployment rate. Specifically, we employed the extended Augmented Dickey-Fuller test through innovational and additive outlier models. The truncation parameters were selected using the t-sig and F-sig general to specific recursive techniques. Unknown breakpoints were observed, which indicates a strong connection with the data. These dates represent critical periods of policy changes by the government and external shocks. The unit-root tests with trend functions suggest that structural breaks in the macroeconomic variable series are very important and significant when formulating economic policies. The breakpoints can be included in a VAR model as deterministic terms to further improve the forecast/prediction power without affecting the asymptotic properties of the test statistics involved in the analysis.